Simultaneously enhancing strength and toughness of Zr-based bulk metallic glasses via minor Hf addition. (March 2020) - Zhu, Y.H.; Zhu, Z.W.; Chen, S.; Fu, H.M.; Zhang, H.W.; Li, H.; Wang, A.M.; Zhang, H.F.
Abstract: Zr65.5-x Hfx Nb3 Cu13 Ni11 Al7.5 (x = 0.0, 0.5, 1.0, 1.5 and 2.0 at.%) bulk metallic glasses (BMGs) were successfully prepared by copper mold casting. The effects of minor Hf addition on the mechanical properties and fracture mechanisms were investigated. The quasi-static compressive mechanical properties of Zr65.5-x Hfx Nb3 Cu13 Ni11 Al7.5 alloys were significantly improved by Hf addition. The optimum compressive fracture strength ( σ f ) and fracture strain ( ε f ) are 1516 MPa and 2.6%, respectively, for the Zr64.5 Hf1.0 Nb3 Cu13 Ni11 Al7.5 alloy. The impact toughness of the Zr64 Hf1.5 Nb3 Cu13 Ni11 Al7.5 alloy ( A k = 127 kJ/m 2 ) is nearly four times than that of the Zr65.5 Nb3 Cu13 Ni11 Al7.5 alloy ( A k = 33 kJ/m 2 ). The increase of the fracture surface area and the ratio of vein-like patterns regions caused by Hf addition play an important role in fracture energy dissipation under dynamic loading. The dependence of mechanical properties on the Hf content is closely related to the variation of free volume in the current alloys. The relationship between the Hf addition and the free volume change is discussed in detail. These results may provide new insights into simultaneously enhancing the plasticity and toughness of BMGs with minor alloying. Highlights: Compressive properties and impact toughness could be simultaneously enhanced. A model considering the bond shortening was proposed and discussed. The free volume change caused by bond shortening was divided into two categories. The correlation between free volume and mechanical properties is clearly described.